An experimental test: Using rubrics for reflective writing to develop reflection. (June 2019) - Cheng, Michelle W.T.; Chan, Cecilia K.Y.
Highlights: The incorporation of the use of rubrics into reflective writing for students. Experiment showed that the use of rubrics help to promote students' level of reflection in their reflective writing. Undergraduates in general did not have a good understanding of what reflective writing is, and how to properly write it. Considering rubrics as learning resources improves student reflective writing. Abstract: The purpose of this study was to examine the effectiveness of utilising rubrics in reflective writing by investigating the effect on students' work and the perceptions of the students and instructors. A hundred and thirty-four undergraduates attended a one-hour reflective writing workshop. All undergraduates were randomly assigned to three groups ran by three instructors: an experimental group in which rubrics were distributed with detailed explanation, another experimental group in which rubrics were distributed without any explanation (a stimulation of self-learning environment in university), and a control group that received no intervention. Measurements of the reflection levels in students' writing were made by three instructors, who independently marked all the reflective writings based on the same rubric given to the undergraduates. Results revealed that experimental groups acquired significantly higher levels of reflection in students' reflective writings than the control group. However, no significant differences were found between the two experimental groups.